2008
DOI: 10.1016/j.drugpo.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Maximising the highs and minimising the lows: Harm reduction guidance within ecstasy distribution networks

Abstract: Background-Little is known about how users build and share knowledge concerning the highs and lows of Ecstasy and the role that Ecstasy sellers play in the exchange of this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 28 publications
2
41
0
3
Order By: Relevance
“…Sometimes, negative consequences would occur from use. Similar to that found in other research studies [84][85] , drug impurity was also a concern, and adverse reactions to unknown combinations were discussed among several respondents in the EDM scene. As Dublin-a 27 year-old Hispanic male-noted.…”
Section: Miembros Subculturales De La Drogasupporting
confidence: 60%
See 1 more Smart Citation
“…Sometimes, negative consequences would occur from use. Similar to that found in other research studies [84][85] , drug impurity was also a concern, and adverse reactions to unknown combinations were discussed among several respondents in the EDM scene. As Dublin-a 27 year-old Hispanic male-noted.…”
Section: Miembros Subculturales De La Drogasupporting
confidence: 60%
“…Algunas veces, se producían consecuencias negativas del uso. De forma similar a lo encontrado en otros estudios 84,85 , la impureza de la droga era motivo de preocupación, y varios entrevistados de la escena de la MEB hablaron de las reacciones adversas ante combinaciones desconocidas. Como Dublín -un hombre hispano de 27 años-indicó: "La gente se quedaba tocada a causa de las drogas porque no eran drogas, eran otra cosa".…”
Section: Miembros Subculturales De La Drogaunclassified
“…Some researchers have collaborated with the harm reduction organization Dance Safe to explore the use of drug testing kits among recreational ecstasy users at music festivals (Tanner-Smith, 2006;Winston et al, 2001). Aside from drug testing kits, recreational "party drug" users tend to rely on peer-to-peer transmission or word of mouth as the primary means of generating knowledge related to drug use and the adoption of harm reduction strategies to mitigate risk (Tackett-Gibson, 2008;Jacinto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The social settings of ATS consumption are important to consider as they may affect levels and patterns of alcohol and other drug use and associated harms (Boys et al, 1999;Jacinto, Duterte, Sales, & Murphy, 2008;Singer & Schensul, 2011). For example, in a qualitative study of 16-to 21-year-olds, Boys and colleagues (1999) found that participants commonly discussed needing to be in the right sort of environment when taking drugs.…”
Section: Amphetamine-type Stimulants -Effects and Socio-environmentalmentioning
confidence: 99%
“…Stimulant use is inextricably linked to young adults' social environmental settings (Van Havere et al, 2011), and the settings in which ATS are used may contribute to hazardous levels of alcohol consumption (Jacinto et al, 2008;Singer & Schensul, 2011). Licensed venues, particularly nightclubs, are characterized by both alcohol and other drug use (Calafat et al, 2008;Van Havere et al, 2011) and, consequently, may encourage simultaneous use.…”
Section: Introductionmentioning
confidence: 99%